2014
DOI: 10.1371/journal.pone.0106962
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of H3K9 Methyltransferase G9a Repressed Cell Proliferation and Induced Autophagy in Neuroblastoma Cells

Abstract: Histone methylation plays an important role in gene transcription and chromatin organization and is linked to the silencing of a number of critical tumor suppressor genes in tumorigenesis. G9a is a histone methyltransferase (HMTase) for histone H3 lysine 9. In this study, we investigated the role of G9a in neuroblastoma tumor growth together with the G9a inhibitor BIX01294. The exposure of neuroblastoma cells to BIX01294 resulted in the inhibition of cell growth and proliferation, and BIX01294 treatment result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 50 publications
(37 reference statements)
6
63
2
Order By: Relevance
“…Moreover, EHMT2 suppression induces autophagy and represses cell proliferation in neuroblastoma [44, 45] or peritoneal metastasis in ovarian cancer [46]. Although elevated levels of EHMT2 expression have previously been observed in various cancer tissues when compared with normal tissues, the clinical significance of EHMT2 expression in tumors not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EHMT2 suppression induces autophagy and represses cell proliferation in neuroblastoma [44, 45] or peritoneal metastasis in ovarian cancer [46]. Although elevated levels of EHMT2 expression have previously been observed in various cancer tissues when compared with normal tissues, the clinical significance of EHMT2 expression in tumors not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the mitochondrial membrane potential by flow cytometry and found the signally decrease of mitochondrial membrane potential in GA001 treated MCF7 cells ( Figure 6C). Given that G9a is closely associated with cell cycle and DNA damage in different cells [25,28,29], we checked the expression of key cell cycle proteins CDK2 and Cyclin E. We found that GA001 obviously downregulated the expressions of CDK2 and Cyclin E ( Figure 6D). Since the pro-apoptosis protein Bim is negatively regulated by CDK2…”
Section: Ga001 Induces Apoptosis In Mcf7 Cellsmentioning
confidence: 98%
“…BIX01294, a specific inhibitor of G9a29, induced autophagy or autophagy-associated cell death in several tumor cell lines3031323334, but underlying mechanisms have not been explored in glioma cells. Treatment with BIX01294 reduced methylation of H3K9 and H3K27, and at higher concentrations impaired viability of rat C6 glioma cells35.…”
mentioning
confidence: 99%